6.7 Neonatal thyroid function and the use of povidone-iodine and iodinated contrast media during labour and the postnatal period: a pilot study. (9th June 2014) - Williams, FLR; Velten, E; Day, C; Soe, A; Somisetty, S
Abstract : Context: The developing thyroid is sensitive to iodine overload with exposure potentially resulting in goitre and/or hypothyroidism. The British National Formulary (BNF) lists neonates <32 weeks gestation and infants under 1.5 Kg as contra-indications for the use of povidone-iodine for skin disinfection, and recommends its avoidance during pregnancy and breast feeding. The BNF makes no recommendation on the use of iodinated-contrast media, as it is not a listed drug. Existing research in this area is inconsistent and based on small, outdated studies. Aim: Are neonatal thyroid hormone levels in preterm infants changed by maternal, fetal or neonatal exposure to iodine? Methods: Case-comparison study of infants born <32 weeks gestation. Main outcomes: Levels of thyroxine, thyroxine binding globulin and thyroid stimulating hormone (TSH) measured on Guthrie card on postnatal day 7, 14 and 28 and at 36 corrected weeks gestation. Results: 125 infants were potentially exposed and 48 infants not exposed to iodine from contrast media and/or povidone-iodine during labour. 13 infants recorded a TSH ≥6 mU/L in the first 28 days postnatal: 6% of infants were exposed to contrast media, 15% were exposed to povidone-iodine during labour, and 8% had no known exposure. No infants were diagnosed with transient hypothyroidism, 3 infants (exposed to contrast media) had transient hyperthyrotropinaemia (10–19 mU/L). Comment: In the context of this small pilot study, the incidence of raised TSH levels appears higher in infants exposed to iodine during labour but not in those exposed to contrast media. A large study is now planned.